Adherence to post-exposure prophylaxis and associated socio-demographic characteristics of dog bite patients visiting selected health facilities in Kisii County, Kenya - Ogugu, Nickson Okiomeri; Mwanzo, Isaac; Gicheru Muita, Micheal (International Journal Of Community Medicine And Public Health, 2024)
Background: Dog bites have proven to be a significant public health concern among African and Asian countries that report 95% of human mortalities. Rabies is a deadly viral disease spread by a rabid animal that invades the CNS and is 100% fatal. The main objective of the study was to assess adherence to rabies post-exposure prophylaxis and associated socio-demographic characteristics among dog bite patients. Methods: This was a hospital-based cross-sectional study with 289 dog bite patients from selected health facilities in Kisii County, Kenya. Simple random sampling technique was adopted in the selection of participants, while the health facilities were purposively selected. Data was analysed using SPSS software version 25. Results: More than a half (57.8%) of the dog bites were females as compared to their male counterparts (42.2%). Level of education (p=0.001), age (p=0.012), marital status (p=0.001), income (p=0.001) were significant determinants of adherence to rabies PEP treatment, preferred rabies PEP regimen acquired (p=0.001). Over 68.2% of the patients adhered to rabies PEP treatment, adherence to individual dosage of ARV regimen with 67.2% of dog bite patients completed the PEP regimen, ZAGREB regimen had 95.6% of dog bite patients likely to complete their treatment compared to ESSEN regimen. Conclusions: Dog bites were prevalent among females. The study further revealed that as the level of education increased the odds of rabies PEP adherence treatment improved. Dog bite patients preferred ZAGREB rabies PEP regimen.